Use of Antibiotics following Snakebite in the Era of Antimicrobial Stewardship - Helena Brenes-Chacon; José María Gutiérrez; María L. Avila-Aguero (Toxins, 2024)
Even though there are guidelines for the management of snakebite envenoming (SBE), the use of antibiotics in this pathology remains controversial. The aim of this study is to provide a narrative review of the literature and recommendations based on the best available evidence regarding antibiotic use in SBE. We performed a narrative review of relevant literature regarding SBE and antibiotic use as prophylaxis or treatment. A total of 26 articles were included. There is wide use of antibiotics in SBE; nevertheless, infection was not necessarily documented. The antibiotics used varied according to the study, from beta lactams to lincosamide and nitroimidazoles, and from monotherapy to combined antimicrobials. The most common recommendations were to manage skin and soft tissue infections and avoid infectious complications, but these suggestions are not necessarily based on bacteriological findings. Prophylactic use of antibiotics in SBE is discouraged in most studies. Antibiotic prescription in SBE should be based on the susceptibility of microorganisms isolated from the affected tissue or identified in snakes’ oral cavities. Antibiotics should be reserved only for patients with a demonstrated infection, or those at a high risk of developing an infection, i.e., presenting severe local envenoming, local signs of infection, or those with incorrect manipulation of wounds. Prospective studies are needed to correlate microbiological findings at the wound site and the response to antibiotic use.